Individual, parental and built environmental features as influencing factors of active travel to school in northeast China: findings from a cross-sectional study. Issue 1 (24th January 2022) - Wang, Yinuo; Liu, Yang; Song, Shenzhi; Gittelsohn, Joel; Ouellette, Miranda; Ma, Yanan; Wen, Deliang
Abstract : Objectives: Active travel to school (ATS)-associated factors had been studied in some developed countries but rarely in China. We studied the associated factors of ATS at individual, parental and built environment domains in northeast China. Design and participants: A cross-sectional survey was conducted among 4–6 grade students in 2017. Sociodemographic features and information of parents were collected using questionnaires, and SuperMap (a geographical information system software) was used to catch built environment features. Logistic regression models were used to examine the relationship between multilevel factors and ATS. Results: Our study sample comprised 3670 primary school students aged from 8 to 15 (boys=51.0%, ATS=48.8%). Perceived to be fat (OR 1.25, 95% CI 1.00 to 1.55, p<0.05), feeling easy to walk for a short distance (OR 1.63, 95% CI 1.21 to 2.20, p<0.05), mother unemployed (OR 1.52, 95% CI 1.13 to 2.06, p<0.05), higher land use mix (OR 1.23, 95% CI 1.11 to 1.37, p<0.001) and higher density of public transport stations (OR 1.22, 95% CI 1.09 to 1.37, p<0.05) were positively associated with increased possibility of ATS, while higher household annual income (OR 0.60, 95% CI 0.44 to 0.83, p<0.05) and possession of private vehicles (OR 0.56, 95% CI 0.45 to 0.69, p<0.001) were negatively associated with possibility of ATS. Conclusions: The significant factors associated with ATS were at every examined level, which implies multilevel interventions are needed to encourage ATS. Further interventions could focus on the children's willingness to lead students to opt for healthy behaviours, and children from wealthier families should be encouraged to choose ATS. Also, the government should improve built environment walkability so as to encourage ATS.